Zeminin kırmataş kolonları ile iyileştirilmesi - Mungan, Hüseyin (İstanbul Kültür Üniversitesi / Fen Bilimleri Enstitüsü / İnşaat Mühendisliği Anabilim Dalı / Geoteknik Bilim Dalı, 2016)
İstanbul Kültür Üniversitesi, Fen Bilimleri Enstitüsü, İnşaat Mühendisliği Anabilim Dalı, Geoteknik Bilim Dalı Programında yüksek lisans tezi olarak hazırlanan bu çalışmanın amacı; aşırı oturmaların görüldüğü zemin ortamlarında darbeli kırmataş kolonların göstereceği performansların incelenmesidir. Zeminde rijitliği artırmak için yapılan darbeli kırmataş kolonlar, toplam ve farklı oturmaları azaltmaktadır. Bu çalışmada, Plaxis sonlu elemanlar programı kullanılarak, DKK' lar modellenerek, DKK'lı ve DKK'sız ortamda oturma miktarları karşılaştırılarak sonuçlar incelenmiştir. İlk aşamada, 17 m genişliğindeki yayılı temelin yumuşak zemin ortamında 52,55 cm oturma yaptığı görülmüştür. İkinci aşamada, darbeli kırmataş kolonların etkilediği zemin ortamında kompozit zemin modeli esas alınarak, DKK ve zemin parametrelerini kapsayan ortak kompozit bölge tanımlanarak, yayılı temelde 16,87 cm oturma oluştuğu görülmüştür. Üçüncü aşamada, yayılı temel altına 1,7 m aralıklarla kare yerleşim planına göre DKK' lar tanımlanarak, yayılı temelde 26,04 cm oturma oluştuğu görülmüştür. Darbeli kırmataş kolonların, aşırı oturmaların görüldüğü yumuşak zemin ortamlarında, oturmaları önemli derecede azalttığı analizlerde görülmüştür.
Ground improvement with rammed aggregate piers
The essential aim of this thesis that has been prepared in Geotechnical Engineering program of Civil Engineering Department at Istanbul Kültür University, is to analyze the performance of the Rammed Aggregate Piers in the situations that it performs the inserted in soft soils. Rammed Aggregate Piers increase the stiffness of soil, decreasing both total and differential settlements, while increasing the bearing capacity. The study has been performed with the principal aim of comparing the settlements of the untreated soil to that of the soil having been treated by Rammed Aggregate Piers . The software Plaxis 2D which uses the Finite Element method has been employed to analyse the problem. In my study, every work has been done to compare two conditions with each other. These conditions are done both with Rammed Aggregate Piers and without Rammed Agregate Piers. To do this, amount of settlements of Rammed Aggregate Piers is considered and Plaxis FEM program is implemented. A comprehensive literature survey to understand the mechanics of the process was implemented prior to the calculation stage. In the first step a footing of 17 m length was placed on the untreated soil and was found to settle 52,55 cm. The second approach was attempted by assuming the soil-column system as a composite material. This produced a settlement of 16,87 cm. Rammed Aggregate Piers were inserted in the third step in a square pattern with a spacing of 1,7 m, which reduced the settlement to 26,04 cm. As a result of the study, it was confirmed that the use of Rammed Aggregate Piers significantly decreases settlement in soft soils.
Keywords: Darbeli Kırmataş Kolonlar; Sonlu Elemanlar; Oturma; Rammed Aggregate Piers; Settlement; FEM